PENGELOLAAN MEDIA ONLINE WEBSITE DALAM PENYEBARLUASAN INFORMASI PUBLIK OLEH DINAS KOMUNIKASI, INFORMATIKA DAN STATISTIK PROVINSI RIAU TAHUN 2016 - Sri Wulandari; Muchid " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
In this digital era, public information is one of the biggest demands on the government. Online media is one of the media that is very easily accessed via mobile phones, various existing features are expected to help the government in implementing the principle of transparency. Through the website, one of the tools considered to have advantages is in helping the government to implement public information disclosure. Some of the advantages possessed by the website are being able to store and disseminate public information in the form of videos, documents and other forms of data.               This study aims to describe the management and use of online media websites in the dissemination of public information by the Riau Provincial Information and Informatics Communication Service, then to find out the inhibiting factors for the non-optimal implementation of website management by the Riau Communication, Informatics and Statistics Office. The location of the study was conducted at the Office of Informatics and Statistics Communication of Riau Province. Furthermore, this study uses data collection techniques conducted by interviews and documentation. And using a qualitative descriptive approach.               The results of this study are the implementation of online website media management in the dissemination of public information carried out by the Office of Information Communication and Statistics of Riau Province in 2016 is quite good. Some factors that hamper website management in the dissemination of public information are caused by the lack of data to be disseminated through the website, limited budget, the absence of clear SOPs in managing the website, the lack of utilization of available facilities and content and the lack of management commitment in implementing website management. Keywords: Public Information Openness, Management, Online Media, Website, Good Governance, Transparency, Respontability, Participation, Effectiveness and Efficiency.